Upaya Meningkatkan Kesiapan Belajar Statistik Melalui Pemberian Pre-Quiz Pada Mahasiswa Calon Guru SD - Juhari, Agusalim; St. Habibah (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2025)
This study aims to examine the effect of pre-quiz implementation on students' learning readiness in the Statistics course within the Elementary School Teacher Education (PGSD) program at Universitas Negeri Makassar. Using a quantitative approach, an experimental design, and data collection through weekly pre-quizzes over four weeks, the study measured the week-to-week improvement in students' learning readiness. The results indicate a significant increase in students' learning readiness, with the average pre-quiz score rising from 43.16 in Week 1 to 78.95 in Week 4. Descriptive and inferential analyses using the Paired Sample t-Test revealed a significant difference between pre-quiz scores in Week 1 and Week 4, with t-value (5.62) > t-table (1.721) and p-value = 0.000, indicating that the pre-quiz had a positive effect on improving students' learning readiness. This improvement is also reflected in the shift of students into higher readiness categories, with more students moving into the "High" and "Very High" categories in the later weeks. Overall, the findings suggest that pre-quizzes can serve as an effective tool to enhance students' learning readiness, especially in dealing with more complex materials such as statistics. The study recommends that lecturers integrate pre-quizzes into Statistics instruction to improve students' learning preparedness.